Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1951
DOI: 10.1002/hlca.19510340228
|View full text |Cite
|
Sign up to set email alerts
|

Die Konstitution des Alkaloids Cryptolepin

Abstract: Die Gattung Cryptolepis ist eine Asclepiadacee, die sowohl in West-, als auch in Ostafrika vorkommt. Cryptolepisarten sind weder bei Wehmer2), noch bei Perrot3) erwahnt, hingegen finden wir Hinweise auf ihre Verwendung als Stomachica und als Mittel zum Farben von Textilien und Leder bei Watt4), Re%ier5) und DaZzieZ6). Samtliche Cryptolepisarten sind strauchartige Holzpflanzen. Alle besitzen einen gelblichen, bitteren Saft, der sich an der Luft sehr rasch rot fiirbt. Aus den Wurzeln von Cryptolepis triangularis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 8 publications
1
60
0
Order By: Relevance
“…As an activator of p21 WAF1/CIP1 promoter activity, we isolated cryptolepine (CLP: 5-methyl indolo (2,3b)-quiniine), an indoloquinoline alkaloid, from the traditional Ayurvedic medicinal plant Sida cordifolia. CLP was first isolated from Cryptolepis sanguinolenta (24) that is native to Central and West Anti-malaria activity of CLP was reported previously (26). In addition, it has been reported that CLP can suppress the growth of cancer cells in vitro by inhibiting cell cycle progression and causing apoptosis in human HL-60 leukemia (27) and B16 melanoma cells (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…As an activator of p21 WAF1/CIP1 promoter activity, we isolated cryptolepine (CLP: 5-methyl indolo (2,3b)-quiniine), an indoloquinoline alkaloid, from the traditional Ayurvedic medicinal plant Sida cordifolia. CLP was first isolated from Cryptolepis sanguinolenta (24) that is native to Central and West Anti-malaria activity of CLP was reported previously (26). In addition, it has been reported that CLP can suppress the growth of cancer cells in vitro by inhibiting cell cycle progression and causing apoptosis in human HL-60 leukemia (27) and B16 melanoma cells (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…315,316 The total synthesis of 336 was achieved as illustrated in Scheme 72. The total synthesis started from coupling of 1,5-naphthalenediol mono-methoxymethyl (MOM) ether 329 with bromobenzoquinone 330 mediated by K 2 CO 3 in DMSO 317 to afford a C-O coupling product.…”
mentioning
confidence: 99%
“…To compound 13 (1 mmol) in ethanol (10 mL) was added sodium hydroxide (100 mL, 10% w/v) and the mixture refluxed for 2h in a 100 o C oil bath. The cooled mixture was extracted with chloroform (50mL×5), and the extract was dried over MgSO 4 . After removal of the solvent, the residue was chromatographed on silica gel, eluting with light petroleum and ethyl acetate (3:1 to 1:1) to give indolo [3,2-b]quinoline 15 and indolo [3,2-b]quinolinone 17 as yellow solid.…”
Section: Methodsmentioning
confidence: 99%
“…(Figure 1) A number of indolo [3,2-b]quinoline and indolo [3,2-b]quinolinone alkaloids, such as quindoline 1, 1,2 quindolinone 2, 3 cryptolepine 3, 4 5-methylquindolinone 4, 1 biscryptolepine 5, 5 cryptoquindoline 6, 1 cryptomisrine 7 6 etc., had been isolated from a medicinal plant Cryptolepis Sanguinolenta in Africa. (Figure 2) Many indolo [3,2-b]quinoline and indolo [3,2-b]quinolinone derivatives, especially the 11-substituted indolo [3,2-b]quinoline, showed remarkable pharmaceutical activity.…”
Section: Introductionmentioning
confidence: 99%